Influence of socioeconomic factors on the nutritional status of pupils of 5 to 11 in rural areas in cameroon: Case of the Nyambaka municipality in the Adamawa region - Mbarawa Marat Kofia Ibrahim; Mohamadou Lawan Loubou; Kagoue Simeni Luc-Aime; Mohamadou Aminou; Ndoe Guiaro Marcellin (Wolters Kluwer Medknow Publications, 2022)
Malnutrition greatly increases the risk of infant mortality and vulnerability to various diseases later in the long run. It has been shown that children's malnutrition is the result of low household income. Rural areas in Cameroon are mainly made up of poor families. This guided the present research to analyze some socioeconomic factors and their impact on the nutritional status of pupils. Using a simple random sampling technique, 300 pupils were recruited. About 66.33% of pupils were from poor families. Obesity was more prevalent in the category of rich pupils (09.52%) compared to poor (06.53%). The height and weight of pupils studied were lower than the reference (P < 0.001). This study carried out in a single council is proven to be limited for a better understanding of the epidemiology of malnutrition among students, and large-scale studies would be adequate to better prevent and control malnutrition in rural areas.